Using mediation in project disputes based on theory of planned behavior and technology acceptance model - Lee, Chia Kuang; Lee, Mei Sin; Thurasamy, Ramayah (American Society of Civil Engineers (ASCE), 2020)
The construction industry has been afflicted by various contractual issues. Alternative dispute resolution (ADR) methods such as arbitration, mediation, expert review, and adjudication techniques have been used to resolve construction disputes effectively. However, among these types of ADR methods, mediation is less applied in the Malaysian construction industry. To better understand and intervene in the use of mediation, this study tested a model conceptualized based on the theory of planned behavior (TPB) and technology acceptance model (TAM) in explaining the decision to use mediation. Both models posit that behavioral intention is the culmination of decision-making. The conceptualized model was empirically tested with partial least-squares (PLS) modeling, drawing from 65 mediation decision makers specializing in building and civil engineering works. Both measurement and structural models were assessed by SmartPLS version 3.0. The results suggest that intention (INT) toward the use of mediation technique is directly predicted by both attitude (ATT) and perceived behavioral control (PBC). The decision-making process is less desired by the influences of subjective norm (SN) and perceived usefulness (PU). The study concluded several strategies to intervene in the use of mediation through the effects of each critical factor at the end of the paper.